Role of Negotiation in Purchasing and Procurement in Malaysia - Abang, Farhana (Global Journal of Purchasing and Procurement Management, 2023)
Purpose: The study sought to analyze the role of negotiation in purchasing and procurement in Malaysia Methodology: The research was conducted entirely on computers. Secondary data, or data that doesn't require actual observation in the field, are the focus of desk research. Because it requires little more than an executive's time, telephone rates, and directories, desk research is generally seen as a low-cost strategy in comparison to field research. As a result, the research used data that had already been collected and reported. This secondary data was readily available via the internet's digital library and scholarly articles. Findings: The results show that negotiation plays an important role in the purchasing and procurement process in Malaysia. Negotiation allows buyers and sellers to come to an agreement that is mutually beneficial and ensures that the transaction is successful. Negotiation allows buyers and sellers to come to an agreement on delivery times and other factors involved in the transaction. Ultimately, negotiation is an important part of the purchasing and procurement process in Malaysia, and it can help to create mutually beneficial agreements. Unique Contribution to Theory, Practice and Policy: Future research in the field of purchasing and procurement may be grounded in the transaction cost theory and the distributive bargaining theory. Policymakers, researchers, and academics from all across the world will all stand to gain from this study's findings. Executives in charge of national purchasing and procurement initiatives will also use the study's findings to boost negotiations performance across the board. The research suggests that the purchasing and procurement sector should implement negotiation policies to boost the effectiveness of their primary operations and activities.